MENGEMBANGKAN KEMAMPUAN MATEMATIS SISWA MELALUI PENDEKATAN PEMECAHAN MASALAH - Eliterius Sennen; Arnoldus Helmon (PGSD UNIKA SANTU PAULUS RUTENG, 2023)
In managing mathematics learning activities, teachers should think about changing and developing learning processes and management to enable students to have mathematical abilities. The management of memorization learning should be changed and developed into meaningful learning, namely learning that provides space and opportunities for students to not only actively accept knowledge as it comes out of the teacher's mouth but must be able to understand it as a basis to be able to apply the knowledge received to solve problems faced in new contexts and situations. This paper is a literature review that seeks to reveal the use of problem-solving approaches in an effort to improve the mathematical abilities of students in mathematics learning at school. Mathematical ability is a practical ability in terms of utilizing mathematical concepts that have been learned in school to solve concrete problems in everyday life. Efforts to develop mathematical skills of students can be done through the management of mathematical learning with a problem-solving approach. Problem solving through problem solving approach can be done following steps: (1) understanding of the problem, (2) planning for problem solving, (3) Implementing problem solving planning, and (4) Looking back at the solution.